PENGARUH PERENCANAAN PARTISIPATIF TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA TOUNDANOUW SATU KECAMATAN TOULUAAN KABUPATEN MINAHASA TENGGARA - RUMENGAN, EOUDIA; POSUMAH, JOHNNY HANNY; DENGO, SALMIN (Sam Ratulangi University, 2019)
The purpose of this study was to determine the effect of participatory planning oncommunity participation in the Development of the Village of Toundanouw Satu Sub-district ToulToul Minahasa District of Southeast. This research uses quantitative methods. The researchrespondents were 30 people from Toundanouw Desa One community who were taken by randomsampling. The instruments and data collection techniques used were questionnaires and assisted withstructured interviews (interview quide). The analysis technique used to test the hypothesis of simplecorrelation statistical analysis or product moment chore. Based on the results of data analysis,conclusions can be drawn: (1) Participatory planning has a positive and significant impact oncommunity participation in village development. The better participatory planning in villagedevelopment, the higher the community participation. (2) Participatory planning in villagedevelopment has a correlation and a significant determination / determination power on communityparticipation. Significant changes in the level of community participation in village development aredetermined by participatory planning in village development. Based on these conclusions, it isrecommended that participatory planning in village development should involve all elements ofstakeholders in the community, namely not only village officials, BPD, and LPMD, and communityleaders / leaders, but also representatives of community groups in villages such as groups farmers,women's groups, youth groups, and others.Keywords : Participatory Planning, Village Development, Community Participation.